Evaluating the Students’ Ability in Using Preposition of Place in Speaking Performance - Imanuel Kamlasi (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
The use of preposition of place in speaking performance still becomes problems for students. Therefore; it is important to evaluate the students’ ability in using preposition of place. This research aimed at evaluating the students’ ability and describing the problems faced by students in using prepositions of place in speaking performance.The descriptive qualitative method was applied in this research. The instrument of this research was an oral test. To get the data, the researcher used Tape Video Recorder (TVR). There were 25 participants of the first semester students of English study program of Timor University chosen randomly as the sample in this research. There were four steps used in analyzing the data, namely transcribing, codifying, analyzing and describing.The results of the research showed that five students passed and nineteen students failed in the test. The highest score was 80,95 and the lowest score was 31. There was one student categorized as very good; two students were categorized as good; three students were categorized as enough; eleven students were categorized poor and seven students were categorized as very poor. For the kind of preposition; the highest percentage was IN which was 67,53%. Then it was followed by ON which was 57,32%. The preposition BEHIND made 55,51% which was higher than NEAR/CLOSE which was 51,56% but it is lower than IN FRONT OF which was 56,57%. The preposition UNDER was 48,39% which was higher than AT. The lowest percentage was preposition AT which was 47,94%.. The students’ average score was 54,60. Therefore the students’ level of ability was categorized as poor. This means that the students failed in using prepositions of place in speaking performance.